2017
DOI: 10.1186/s13104-017-2534-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of glucose control in children and adolescents with type 1 diabetes: results of a cross-sectional study in Cameroon

Abstract: BackgroundIn sub-Saharan Africa the prognosis of children with type 1 diabetes is poor. Many are not diagnosed and those diagnosed have a dramatically reduced life expectancy (less than one year). The purpose of this study was to identify the predictors of glucose control in children and adolescents with type 1 diabetes.MethodsThis hospital based cross-sectional study involved 76 children/adolescents (35 boys and 41 girls, mean age of 15.1 ± 3.1 years) with type 1 diabetes included in the “Changing Diabetes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…Further, the vast majority of prior studies on dysglycemia among African populations have focused primarily on diabetes, with limited inclusion of prediabetes. 13,33,34 Our finding of the potentially large burden of prediabetes in Namibia portends a potentially large future epidemic of diabetes, underscoring the need for Namibian health authorities to prepare to manage commonly concurrent burdens of vascular disease and kidney disease among their citizens. Moreover, Namibia and other SSA countries are undergoing a demographic transition that may hasten the population's progression to diabetes; as death from infection declines, these populations age and develop other risk factors, including obesity, that can hasten the onset of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Further, the vast majority of prior studies on dysglycemia among African populations have focused primarily on diabetes, with limited inclusion of prediabetes. 13,33,34 Our finding of the potentially large burden of prediabetes in Namibia portends a potentially large future epidemic of diabetes, underscoring the need for Namibian health authorities to prepare to manage commonly concurrent burdens of vascular disease and kidney disease among their citizens. Moreover, Namibia and other SSA countries are undergoing a demographic transition that may hasten the population's progression to diabetes; as death from infection declines, these populations age and develop other risk factors, including obesity, that can hasten the onset of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 90%
“…Further, the vast majority of prior studies on dysglycemia among African populations have focused primarily on diabetes, with limited inclusion of prediabetes . Our finding of the potentially large burden of prediabetes in Namibia portends a potentially large future epidemic of diabetes, underscoring the need for Namibian health authorities to prepare to manage commonly concurrent burdens of vascular disease and kidney disease among their citizens.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent findings were illustrated by Soheilipour F et al (2015), [39] as they suggested that higher mothers' awareness is positively correlated with better blood sugar control in their children which was mainly mediated by their socioeconomic status. Furthermore, Niba LL et al (2017) [40] asserted that minimal maternal involvement as a primary caregiver in self-care practices of their diabetic children were significantly associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents, such management activities involve collaborating and communicating with parents and healthcare providers, setting future healthy lifestyle goals, and performing problem‐solving activities (Schilling et al, 2009). Self‐management in adolescents is challenging, and glycemic control is typically at its worst in the transitional period between adolescence and adulthood (Czenczek‐Lewandowska et al, 2019; Niba et al, 2017). One longitudinal study determined that adolescents with adaptive self‐management patterns at baseline exhibited superior glycemic control two years later compared with those in maladaptive self‐management groups (Rohan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%